1998
DOI: 10.1046/j.1365-3024.1998.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Fc‐binding molecules specific for human IgG1 and IgG3 are present in Echinococcus granulosus protoscoleces

Abstract: In this work we describe the presence of Fc-binding activity on the suckers and tegument of E. granulosus protoscoleces. A fraction (PSA-Fc+) from protoscolex somatic antigens was isolated by affinity chromatography on human Fc-gamma1-Sepharose. Analysis by SDS-PAGE of PSA-Fc+ showed that it contained two major components. Using mouse F(ab')2-human Fc chimaeric monoclonal antibodies we verified that PSA-Fc+ bound mainly to human Fc-gamma1 and Fc-gamma3 isotypes. In addition, one of the components of PSA-Fc+ sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Thus, early T-independent antibody responses could be a common phenomenon in experimental infection by Echinococcus spp . Moreover, regarding the isotype restriction reported here it is interesting to note that tegument and suckers of E. granulosus protoscoleces have Fc-like receptors able to bind human IgG1 and IgG3 antibodies trough their specific Fc portions [33]. Such isotypes structurally and functionally correspond to murine IgG2a and IgG2b, respectively [34]; and therefore local IgG2b specific induction in early stages of infection could be seen as a possible evasion strategy exploited by E. granulosus .…”
Section: Discussionmentioning
confidence: 66%
“…Thus, early T-independent antibody responses could be a common phenomenon in experimental infection by Echinococcus spp . Moreover, regarding the isotype restriction reported here it is interesting to note that tegument and suckers of E. granulosus protoscoleces have Fc-like receptors able to bind human IgG1 and IgG3 antibodies trough their specific Fc portions [33]. Such isotypes structurally and functionally correspond to murine IgG2a and IgG2b, respectively [34]; and therefore local IgG2b specific induction in early stages of infection could be seen as a possible evasion strategy exploited by E. granulosus .…”
Section: Discussionmentioning
confidence: 66%
“…Polyclonal B cell activation (86,87) and parasite Fc-like receptors (88)(89)(90)(91) are thought to be partially responsible for anti-parasite ineffective humoral responses. In diverse infection models of strong polyclonal B cells responses, the most common isotypic distribution pattern is characterized by an increase in IgG2 subclasses (87,(92)(93)(94).…”
Section: Discussionmentioning
confidence: 99%
“…Proteases secreted by T. cruzi trypomastigotes can enzymolyze the Fc fragment of normal IgG, suggesting that the FcRs inhibit the cytotoxic effects of the classical pathway 38 39 . Furthermore, a fraction (PSA-Fc + ) isolated from the suckers and tegument of E. granulosus protoscoleces was described to possess proteolytic activity specific for human IgG1 and IgG3 through Fc binding 40 . In the present study, we identified six cathepsins in S. japonicum that exhibited an affinity for human Igs.…”
Section: Discussionmentioning
confidence: 99%